Environmental filtering underpins the island species—area relationship in a subtropical anthropogenic archipelago. (10th September 2019) - Liu, Jinliang; Matthews, Thomas J.; Zhong, Lei; Liu, Jiajia; Wu, Donghao; Yu, Mingjian
Abstract: Numerous mechanisms have been proposed to explain the island species–area relationship (ISAR), including the passive sampling effect, the habitat diversity effect, ecological drift and a group of mechanisms jointly termed environmental filtering (or abiotic selection process). However, determining which of these hypotheses underpins the ISAR in a given system remains an open and controversial question, particularly with regards to the environmental filtering. The effect of environmental filtering on the ISAR for woody plants was tested on 29 islands in a subtropical land‐bridge archipelago. Island area had a significant effect on species richness, while isolation was not found to have an effect. After controlling for the passive sampling effect and habitat diversity using a systematic sampling design, we found that a positive ISAR remained. After controlling for island area and isolation, species richness was significantly affected by environmental conditions (e.g. total phosphorus, soil depth and bulk density). When a null model was used that randomly assigned individuals to islands from the regional pool, the difference between the observed and expected richness was greater for smaller islands relative to larger islands. Synthesis . Our results point to an overlooked role of environmental filtering in driving the island species–area relationship (ISAR). Consequently, our study highlights the importance of considering deterministic process in future analyses of the ISAR. Abstract : By controlling sampling effect and habitat diversity, we found that environmental filtering, which has been rarely tested in previous island species–area relationship (ISAR) studies, is one of the main mechanisms underpinning ISAR in an anthropogenic archipelago. Foreign Language Abstract 摘要: 生态学家已提出很多解释岛屿种—面积关系形成的机制/假说，例如取样效应、生境多样性效应、生态漂变以及与环境过滤（非生物选择）作用相关的假说。然而，在一个研究系统中，如何确定上述何种机制尤其是环境过滤作用支持岛屿种—面积关系仍存在争议。本研究选取浙江千岛湖片段化景观中29个陆桥岛屿，分析了环境过滤作用对岛屿上木本植物种—面积关系的影响。结果发现，岛屿面积而不是隔离度显著影响了岛屿上的物种丰富度，当控制岛屿上的取样效应和生境多样性时，正的岛屿种—面积关系仍然存在。在控制岛屿面积和隔离度对物种丰富度的作用之后，岛屿上的物种多样性受环境因子如土壤总磷、土层厚度和土壤容重显著影响。此外，结合零模型分析发现，当区域物种库内的个体被随机分配到各岛屿上，并保持各岛屿上的总个体数与实际个体数一致时，从零模型中获得的预期物种数均显著低于岛屿上实际观察到的物种数，且岛屿上实际物种数与预期物种数的绝对差异随岛屿面积的减少而增大。本研究的结果表明，环境过滤作用在岛屿种—面积关系的形成中是不可被忽视的，故而在岛屿种—面积关系的相关研究中，需要考虑决定性过程在其中所起的作用。